2022
DOI: 10.1155/2022/9603185
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Oxygen Tension (2%) Is Beneficial for Blastocyst Formation of In Vitro Human Low-Quality Embryo Culture

Abstract: Objectives. To investigate whether a reduction in the O2 tension from 5 to 2% during extended culture from day 3 onwards was beneficial to human blastocyst development in vitro. Methods. We firstly identified 139 patients who had no low-quality embryos on day 3, and all the embryos were prolonged to culture on day 5 or 6. We mainly analyzed 188 patients receiving IVF/ICSI-ET for the first time, and no high-quality embryos were obtained on day 3 from January 2018 to December 2019. After transferred with one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding the use of low oxygen tension, we analyzed 10 studies, generating a LS of 7, suggesting medium evidence of superiority for 5% over 20% oxygen tension. On the other hand, assessing the efficacy of biphasic (5-2%) compared to monophasic (5%) culture, despite the use of biphasic oxygen, seems to have benefits in terms of blastulation; we obtained a low LS of 5, suggesting no evidence of superiority for biphasic over monophasic culture [29][30][31][32][33]. In our temperature analysis, we reviewed a total of 9 [34][35][36][37][38][39][40][41][42] studies, 6 of which were used to calculate the LS.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Regarding the use of low oxygen tension, we analyzed 10 studies, generating a LS of 7, suggesting medium evidence of superiority for 5% over 20% oxygen tension. On the other hand, assessing the efficacy of biphasic (5-2%) compared to monophasic (5%) culture, despite the use of biphasic oxygen, seems to have benefits in terms of blastulation; we obtained a low LS of 5, suggesting no evidence of superiority for biphasic over monophasic culture [29][30][31][32][33]. In our temperature analysis, we reviewed a total of 9 [34][35][36][37][38][39][40][41][42] studies, 6 of which were used to calculate the LS.…”
Section: Discussionmentioning
confidence: 87%
“…A sibling zygote randomized control trial showed, although a small sample size, better blastulation rate when oxygen tension is reduced from 5% to 2% on day 3 for extended embryo culture (day 5) [7], in contrast to two studies that showed a similar blastocyst formation rate between 2%, 5% and 20% oxygen tension [8,28]. One report showed that blastocyst utilization rate is higher in 2% oxygen tension group [29], according to another study that showed improvement in blastocyst formation but only in low-quality human embryos cultured with 2% oxygen [30]. No significant difference were found between 5% and 3% oxygen tension in fertilization, blastulation and euploid blastocyst [31].…”
Section: Oxygenmentioning
confidence: 92%
“…On the contrary, Broillet et al, in an observational retrospective study, reported a significant improvement in the total and usable blastocyst rates as well as a higher cumulative birth rate with the biphasic (5-2%) oxygen concentration strategy [76]. Recently, Li et al reported that the biphasic strategy (5-2% O 2 ) resulted in a better blastulation rate for low-quality cleavage embryos, but not for high-quality cleavage embryos [77]. The most recent study is a retrospective cross-sectional one that found only marginal benefits with the biphasic (5-2%) oxygen strategy: they performed both fresh and frozen embryo transfers, finding that there was no difference in the pregnancy and implantation rates although, in fresh embryo transfers, the implantation rate of embryos cultured with the biphasic oxygen strategy was significantly better [78].…”
Section: Culture Of Human Embryos Under Low Oxygen Levelsmentioning
confidence: 98%
“…According to a recent study, biphasic O 2 (5-2%) has bene cial effects on pre-and peri-implantation embryonic development in mice 11 ; biphasic O 2 may be appropriate for human blastocyst formation 6 . In addition, biphasic O 2 (5-2%) tension culture may be advantageous for patients with poor embryonic development by increasing the number of available high-quality blastocysts 12 .…”
Section: Introductionmentioning
confidence: 99%